Analyse the effect of carbon fiber reinforced polymer (CFRP) strengthening of beams using ANSYS - Sabiha Barour; Abdesselam Zergua; Farid Bouziadi; Waleed Abed Jasim (Journal of Building Materials and Structures, 2024)
This paper presents a nonlinear finite element model analysis to effect of carbon fiber reinforced polymer (CFRP) strengthening of beams using ANSYS, Finite element software ANSYS 12.0 has been used for modeling the beams by conducting nonlinear static analysis. The SOLID 65 and SHELL 181, LINK180 elements have been used to, respectively; model the 3D concrete beams and the composite layer, steel rebars. The results of the finite element were compared with the experimental data The results showed that the general behavior of the finite element models represented by the load-deflection curves shows good agreement with the test data from the previous researches.